2014
DOI: 10.1136/practneurol-2014-000821
|View full text |Cite
|
Sign up to set email alerts
|

A practical approach to, diagnosis, assessment and management of idiopathic intracranial hypertension

Abstract: Adult patients who present with papilloedema and symptoms of raised intracranial pressure need urgent multidisciplinary assessment including neuroimaging, to exclude life-threatening causes. Where there is no apparent underlying cause for the raised intracranial pressure, patients are considered to have idiopathic intracranial hypertension (IIH). The incidence of IIH is increasing in line with the global epidemic of obesity. There are controversial issues in its diagnosis and management. This paper gives a pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 38 publications
2
77
0
8
Order By: Relevance
“…suggested in the revised diagnostic criteria for pseudotumor cerebri syndrome (Table 2) [Friedman et al 2013]. Other symptoms and clinical signs include dizziness, nausea, reduced memory and concentration and horizontal diplopia due to sixth nerve palsy [Carta et al 2004;Mollan et al 2014;Yri and Jensen, 2015;Yri et al 2012]. Recent studies demonstrated a marked cognitive dysfunction [Kharkar et al 2011;Yri et al 2014a;Zur et al 2015] and indicated that impaired executive function, working memory, processing speed and reaction time remained after normalization of ICP and alleviation of the headache and the visual symptoms [Yri et al 2014a].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…suggested in the revised diagnostic criteria for pseudotumor cerebri syndrome (Table 2) [Friedman et al 2013]. Other symptoms and clinical signs include dizziness, nausea, reduced memory and concentration and horizontal diplopia due to sixth nerve palsy [Carta et al 2004;Mollan et al 2014;Yri and Jensen, 2015;Yri et al 2012]. Recent studies demonstrated a marked cognitive dysfunction [Kharkar et al 2011;Yri et al 2014a;Zur et al 2015] and indicated that impaired executive function, working memory, processing speed and reaction time remained after normalization of ICP and alleviation of the headache and the visual symptoms [Yri et al 2014a].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Idiopathic intracranial hypertension (IIH), or pseudotumor cerebri, formerly called benign intracranial hypertension, is a challenging condition with raised intracranial pressure (ICP) in the absence of identifiable cause [Friedman et al 2013;Mollan et al 2014;Friedman, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Where there is no apparent underlying cause for the raised intracranial pressure, patients are considered to have idiopathic intracranial hypertension (IIH). (12) At the moment IIH is confirmed, up to 90% of patients already have various degrees of visual impairment and 10 to 24 % finally progress to permanent severe visual impairment. Visual loss can occur any time along the course of the disease and is usually insidious.…”
Section: Diagnosismentioning
confidence: 99%
“…• Endocrine diseases, for example, Addison's/ Cushing's/hypothyroidism; • Drugs associated with pseudotumour cerebri: (12) -Tetracycline/minocycline/doxycycline; -Corticosteroids; -Beclometasone; -Nitrofurantoin; -Tamoxifen; -Sulphonamides, for example, trimethoprim; -Ciclosporin; -Nalidixic acid; -Non-steroidal anti-inflammatory drugs; -Vitamin A excess and retinoids; -Cimetidine; -Lithium; -Depo Provera.…”
Section: Papilloedemamentioning
confidence: 99%
See 1 more Smart Citation